Deficiencies in Project Governance: An Analysis of Infrastructure Development Program - Khan, Asadullah; M., Waris; Ishak, Ismail; Mirza, Rizwan Sajid; Ullah, Mehfooz; Usman, Faizal (MDPI, 2019)
The governance of public sector infrastructure projects became an important topic of interest in the project, program, and portfolio management literature during the last decade. Today, it is becoming a central focus for policymakers seeking to ensure success in selecting, designing, and implementing government-sponsored programs of multi-projects. Due to the multiple underlying risks and complexities, the governance of infrastructure programs constitutes a critical element in strategic planning in developing countries. This paper has analyzed the infrastructure development program in Gilgit-Baltistan (Northern Pakistan), and revealed major shortcomings in the areas of decision-making, stakeholder management, and role ambiguity. Approaches to remedy these shortcomings have, thus, been proposed.